2019
DOI: 10.1136/bcr-2018-226514
|View full text |Cite
|
Sign up to set email alerts
|

Severe leptospirosis in a patient with positive serological test for spotted fever rickettsiosis

Abstract: Here, we report a case of a 64-year-old man with severe leptospirosis infected in an area in Japan that is non-endemic to leptospirosis. Initially, findings of high-grade fever, mild generalised arthralgia, rashes on the trunk, mild thrombocytopenia, elevated liver enzymes and renal dysfunction led to the suspicion of rickettsiosis, which was an endemic infectious disease in the area. Subsequently, leptospirosis was also considered after carefully reviewing patient history, which revealed that he may have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The concomitant seroprevalent and seroincident findings provide evidence of individuals in Urabá, Colombia, who have been exposed to both microorganisms without developing overt clinical disease or being diagnosed. Our result carries important public health implications, as clinical case reports have indicated that individuals susceptible to concurrent infections by rickettsioses and leptospirosis may experience more severe clinical manifestations and potentially fatal outcomes( 18 , 22 ).…”
Section: Discussionmentioning
confidence: 81%
“…The concomitant seroprevalent and seroincident findings provide evidence of individuals in Urabá, Colombia, who have been exposed to both microorganisms without developing overt clinical disease or being diagnosed. Our result carries important public health implications, as clinical case reports have indicated that individuals susceptible to concurrent infections by rickettsioses and leptospirosis may experience more severe clinical manifestations and potentially fatal outcomes( 18 , 22 ).…”
Section: Discussionmentioning
confidence: 81%
“…We also observed Rickettsia spp. in confirmed leptospirosis cases; this coinfection has been associated with severe leptospirosis [ 75 ].…”
Section: Discussionmentioning
confidence: 99%